Business Models Based on Technology for Startup - Dhanar Intan Surya Saputra; Kuat Indartono; Sitaresmi Wahyu Handani (Journal of Innovation in Business and Economics, 2019)
The many and existence of startups in Indonesia and the world continue to increase, along with the increasing use of technology and the internet. This encourages startups, newcomers to compete and survive to attract the attention of consumers. One of the determinants of startups' success is the business models, especially those related to technology. The use of the right business model will bring the impact of consumer or user trust on the startup. In this paper, the author presents a theoretical reviews related to some technology-based business models trends that can be used by a startup in starting his business as well as how to determine the right business model.